Emotionally entwined narratives: a polyphonic trialogue on learning disability history research - Barden, Owen (My University, 2025)
This paper offers a critical analysis of the concept of “emotional community” in the context of our research into histories of learning disability Emotional communities are places where people feel, express and make sense of emotions. They help us to understand that emotions are something we experience socially and not just individually. The paper is presented in the form of a conversation between many researchers. This is what we mean by “polyphonic”, which translates as “many voices”. Some of us have learning disabilities, and some of us do not. Although there are many voices, the authors belong to teams who worked on three learning disability history projects. Each team comprises researchers and self-advocates with learning disabilities and academics without. We use the word “trialogue” to mean discussion involving the three teams. In the discussion, we first talk about what we mean by “emotional community”. Then we talk about the purpose of emotional communities, and their “light” (good) and “dark” (bad) aspects. We also talk about a process called “commoning”, which is working to understand what we have in common. This leads into a discussion of the ethics of emotional communities. We conclude by reflecting on some of the possibilities and problems we see with emotional communities.
PUBLISHED
Keywords: Emotions, Emotional community, Learning disability studies, Critical disability studies, Inclusive research, Autobiography, Polyphonic conversation, Activism; Identities in Transformation; Inclusive Society; Manuscript, Book and Print Cultures; Disability Inclusion; INTELLECTUAL DISABILITY; Inclusive pedagogy for adults with intellectual disabilities; Inclusive research; LEARNING DISABILITY; Participatory Research Methods; Intellectual Disability; Attitudes; Advocacy and political participation; Social exclusion; Social participation